Safety assessment of preventive pressurized intraperitoneal aerosol chemotherapy in combined treatment of gastric cancer: preliminary results - N. Ya. Muratova; I. V. Kolobaev; D. D. Kudryavtsev; E. I. Smolenov; A. B. Ryabov; V. M. Khomyakov; L. O. Petrov; S. A. Ivanov; A. D. Kaprin (Исследования и практика в медицине)
Purpose of the study. Preventive pressurised intraperitoneal aerosol chemotherapy (PIPAC) safety assessment in the combined treatment of gastric cancer (GC).Patients and methods. The study included 48 patients with morphologically confirmed resectable GC and cardio esophageal transition, having at least one criterion that is a predictor of the development of peritoneal carcinomatosis, e. g. tumor spread to the serous layer (≥ T4a), diffuse tumor type, affected regional lymph nodes, large tumor, young age (up to 45 years), subtotally and totally affected stomach. 36 out of those patients received treatment according to the protocol. All patients received 4 cycles of neoadjuvant chemotherapy according to the FLOT scheme, radical surgical treatment in combination with a PIPAC session, 4 cycles of adjuvant chemotherapy according to the FLOT scheme. The safety assessment was carried out according to the classification of surgical complications according to Clavien-D indo and the international scale for toxicity scaling NCI–CTCAE v5.0.Results. Postoperative complications were diagnosed in 25 %, >III grade complications were revealed in 11 % of cases according to the Clavien-D indo classification. The postoperative mortality rate was 0 %.Conclusion. Preventive PIPAC of locally advanced GC and CET in combined treatment is a reproducible and safe method, which is characterized by the absence of an increase in the number of postoperative complications and mortality rate.